The Srategy of Provincial Library on Managing Disability Service: Case Study of Modern Regional Library South East Sulawesi - Hera Pebrianti,; Inawati, (Literatify : Trends in Library Developments, 2023)
Disability services in libraries at the provincial level are critical for promoting equal access, fostering inclusivity, and ensuring that libraries are welcoming spaces for everyone in the community, regardless of their abilities or disabilities. This study aims to identify the strategy of Modern Regional Library South East Sulawesi Province Library on Managing Disability Service. Thus, this study used a qualitative method. For qualitative data collection techniques, conducting interviews with librarians of Modern Regional South East Province and five librarians in that library. In conclusion, The first, the financial strategy carried out is good but currently Modern libraries have not focused on disability services which should also need attention. The second, the facility management strategy is also not optimal because the facilities provided are still very lacking while there are many visitors for disability services, especially from the Special School (Disability School) in Kendari city often send official letterss to the library to make visits. Libraries need to create an inclusive and welcoming space for all members of the community. The third, libraries in charge of disability services are still lacking and there are no special librarians who can speak sign language. This indicates that libraries also need to maximize their Human Resources management strategies. Finally, the library organization development strategy actually has plans for disability services in the future and partners with the national library of Indonesia, and companies in the city of Kendari to improve disability services, but still needs careful planning so that in the future library services can be accessed by people with special needs with adequate facilities.